2022
DOI: 10.3390/vaccines10081342
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination for Monkeypox Virus Infection in Humans: A Review of Key Considerations

Abstract: Monkeypox virus infection in humans (MVIH) is currently an evolving public health concern given that >3000 MVIH cases have been reported in >50 countries globally, and the World Health Organization declared monkeypox a global health emergency on 23 July 2022. Adults (≥16 years old) usually have mild disease in contemporary studies, with a pooled case fatality rate of 0.03% (1/2941 cases). In comparison, poorer outcomes have been reported in children <16 years old (pooled case fatality rate 19% (4/21 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 62 publications
0
47
0
Order By: Relevance
“…The smallpox vaccine has gone through three genera_tions of medical technology but only the second and third generation vaccines are currently licensed: ACAM2000, a replication-competent smallpox vaccine, and IMVANEX (also known as JYNNEOS or IMVAMUNE; Bavarian Nordic, Hellerup, Denmark), a live, nonreplicating vaccine. 141 These can be used in two situations: pre-exposure to prevent infection and disease among those at high risk, or post exposure (ideally within 4 days of exposure) to improve infection and disease outcomes. 142…”
Section: Vaccinationmentioning
confidence: 99%
“…The smallpox vaccine has gone through three genera_tions of medical technology but only the second and third generation vaccines are currently licensed: ACAM2000, a replication-competent smallpox vaccine, and IMVANEX (also known as JYNNEOS or IMVAMUNE; Bavarian Nordic, Hellerup, Denmark), a live, nonreplicating vaccine. 141 These can be used in two situations: pre-exposure to prevent infection and disease among those at high risk, or post exposure (ideally within 4 days of exposure) to improve infection and disease outcomes. 142…”
Section: Vaccinationmentioning
confidence: 99%
“…260 In the current 2022 monkeypox outbreak, it was reported that patients at least sixteen years old always have milder symptoms in the current investigations, with a pooled case fatality rate of 0.03% (1 of 2941 patients). 279 Monkeypox is more often fatal in children, which is similar to smallpox. 36,80 As of September 2022, a total of 15 deaths have been documented in this monkeypox global outbreak, in which 9 deaths in locations that have historically recorded monkeypox.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Owning to immunological cross protection among orthopoxviruses, 194,298,[394][395][396][397][398] smallpox vaccines (vaccinia virusbased) were recommended for use in the current outbreak of monkeypox. 279,[399][400][401][402][403][404][405] Epidemiological data on human monkeypox collected in Zaire from 1980 to 1984 revealed that there was a significant difference in attack rates between contacts without a vaccination scar and those who had been vaccinated in the past (7.2% vs. 0.9%). 406 Rimoin et al suggested that monkeypox incidence increased dramatically in the DRC 30 years after smallpox vaccination campaigns ended.…”
Section: Monkeypox Preventionmentioning
confidence: 99%
“…There are 2 types of vaccines: second and third generation. Second generation vaccines called replication competent vaccinia virus vaccines due to their replication capacity in mammalian cells (examples ACAM2000 and APSV approved for > 18 years old) that are associated with complications or adverse events that can be severe amongst immunocompromised individuals with no safety study in HIV population or pregnant population [5,6]. For example, after vaccination with these vaccines, we can have common local side eff ects such as pain, erythema or induration and common systemic side eff ects such as fever, chills, fatigue, myalgia, headache, nausea that are generally mild and transient [6].…”
Section: Discussionmentioning
confidence: 99%